Upaya Mahasiswa KKN STKIP Hamzar Mewujudkan Zero Stunting di Dusun Langgar Sari dan Nyangget Desa Jenggala Kabupaten Lombok Utara - Sartika, Amelia; Musafir, Musafir; Habiburrahman, Lalu; Jannah, Rauhun; Juniarti, Tina; Susianti, Emi; Aini, Finatul; Islamiah, Nilatul (Universitas Mataram, 2024)
Stunting is a national problem, in addition to national problems, it was also raised as the theme of KKN STKIP Hamzar 2024. This stunting is one of the foundations of community service. Community service located in Jenggala village. Jenggala village is one of the villages with a high stunting rate. Most of the people (parents) of Jenggala village are busy which results in no time to pay attention to their children's eating patterns. To overcome this, KKN STKIP Hamzar Jenggala village students carried out several work programs as an effort to overcome problems in society regarding stunting, namely, socialization of stunting prevention, training in Making Simple Additional Food (PMT), with simple ingredients that do not require much time but are rich in nutrients as well as distribution to children and pregnant women, planting moringa trees, introducing the benefits of moringa leaves. Moringa leaves or Moringa oleifera have long been known in Indonesia as a rich source of nutrition and have various benefits. In the context of preventing stunting, moringa leaves offer interesting potential because of their complete nutritional content. This activity cannot be separated from the collaboration of KKN STKIP Hamzar students with the Jenggala Village government, Tanjung District, North Lombok Utara.